Clinical factors linked to the type of respiratory medication in COPD: results from the COSYCONET cohort - Alter, Peter; Kahnert, Kathrin; Trudzinski, Franziska; Bals, Robert; Watz, Henrik; Speicher, Tim; Söhler, Sandra; Welte, Tobias; Rabe, Klaus F.; Wouters, Emiel F. M.; Vogelmeier, Claus F.; Jörres, Rudolf (Therapeutic advances in respiratory disease, 2023)
Background: The use of maintenance medication in patients with chronic obstructive pulmonary disease (COPD) in real life is known to deviate from recommendations in guidelines, which are largely based on randomized controlled trials and selected populations. - Objectives: We used the COSYCONET (COPD and Systemic Consequences - Comorbidities Network) cohort to analyze factors linked to the use of COPD drugs under non-interventional circumstances. - Design: COSYCONET is an ongoing, multi-center, non-interventional cohort of patients with COPD. - Methods: Patients with COPD of Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades 0-4 participating in visits 1-5 were included. Data covered the period from 2010 to 2018. Generalized linear models were used to examine the relation of COPD characteristics to different types of respiratory medication. - Results: A total of 1043 patients were included. The duration of observation was 4.5 years. Use of respiratory medication depended on GOLD grades 0-4 and groups A-D. Long-acting muscarinic antagonist therapy increased over time, and was associated with low carbon monoxide (CO) diffusing capacity, while inhaled corticosteroid (ICS) use decreased. Active smoking was associated with less maintenance therapy in general, and female sex with less ICS use. From the eight items of the COPD Assessment Test, only hill and stair climbing were consistently linked to treatment. - Conclusion: Using data from a large, close to real-life observational cohort, we identified factors linked to the use of various types of respiratory COPD medication. Overall, use was consistent with GOLD recommendations. Beyond this, we identified other correlates of medication use that may help us to understand and improve therapy decisions in clinical practice. - Trial registration: ClinicalTrials.gov NCT01245933.